2005
DOI: 10.1148/radiol.2363040911
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Preoperative Detection of Artery of Adamkiewicz with Dynamic Contrast-enhanced MR Angiography

Abstract: The artery of Adamkiewicz was detected in a large percentage of patients in whom there were no spinal complications, unlike the spinal complications that occurred in the patients in whom the artery was not detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 19 publications
1
56
1
2
Order By: Relevance
“…For preoperative identifi cation of the AKA and the ASA, several angiographic techniques including selective spinal cord angiography [5,6], MR angiography [12,13], and CT angiography [7][8][9][10][11] B) A 2D curved-MPR demonstrates connection from aorta to anterior spinal artery by the AKA, and its continuity through the collateral circulation ( * ). Red arrow points to AKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For preoperative identifi cation of the AKA and the ASA, several angiographic techniques including selective spinal cord angiography [5,6], MR angiography [12,13], and CT angiography [7][8][9][10][11] B) A 2D curved-MPR demonstrates connection from aorta to anterior spinal artery by the AKA, and its continuity through the collateral circulation ( * ). Red arrow points to AKA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that selective spinal cord angiography [5,6], multi-detector row computed tomography (CT) angiography [7][8][9][10][11], and magnetic resonance (MR) angiography [12,13] are useful for identifying the AKA and the ASA preoperatively. However, the visualization of the AKA and of the continuity between the aorta and the ASA with these techniques may not be adequate to prevent spinal cord ischemia after surgery.…”
mentioning
confidence: 99%
“…4,5,[10][11][12][13] The use of these imaging techniques for preoperative analysis and surgical planning enables selective reconstruction of the feeding radiculomedullary artery. 4,5,14 However, it is di‹cult to reconstruct the artery of Adamkiewicz itself because of its small size (about 0.5 mm in diameter) and its branching from the intercostal/lumbar artery at the intervertebral foramen. Therefore, in the surgical approach, 2 methods are used to maintain the blood ‰ow to the artery of Adamkiewicz.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for detection of the artery of Adamkiewicz in both the original and the 3D-MIP images were as previously reported: 5,7 1) depiction of a clearly deˆned blood vessel connected to the radiculomedullary or lumbar artery in the early phase, 2) depiction of a blood vessel running toward the anterior spinal cord with a hairpin-turn connection in the early phase, and 3) diminished signal intensity of this vessel in the late phase. Using curved MPR images, the vertebral level of ar- terial branching from the aorta and the level at the intervertebral foramen were also evaluated.…”
Section: Detection Criteriamentioning
confidence: 99%
See 1 more Smart Citation